Budaya Organisasi dan Kepuasan Kerja Pada Guru - Umi Anugerah Izzati; Olievia Prabandini Mulyana (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2019)
Every individual who feels satisfied with his work will provide optimal performance. These conditions also occur in the world of education so job satisfaction is an important thing that must be owned by the teacher. Teachers who have satisfaction in their work will try to give their best performance. In fostering a sense of satisfaction with the work of the teachers, it takes the conditions of the workplace or school that can support optimization of performance. The conducive workplace conditions are reflected in the culture that exists in the school and can be felt by the teachers. Therefore this study aims to determine the relationship between organizational culture and job satisfaction in private upper secondary school administrators in Surabaya. This study uses a quantitative approach. This research is a population research that uses the subject of teachers who work in one private high school in Surabaya. The number of subjects of this study were 50 private high school teachers in Surabaya. The instrument used in this study is the scale of organizational culture and job satisfaction scale. The scale of organizational culture in this study was based on Robbins and Coulter's theories. While the job satisfaction scale in this study was based on Spector's theory. Data analysis in this study uses product moment correlation. The results of the product moment analysis (r = 0.670, p <0.05) showed significant results. Thus the research hypothesis is accepted that there is a relationship between organizational culture and job satisfaction among high school teachers. The correlation coefficient of 0.670 indicates the direction of the relationship in this study which is positive, meaning that the better the teacher's perception of organizational culture in schools, the higher job satisfaction experienced by teachers.